Enzyme-linked immunosorbent assay-based inhibition test for neutralizing antibodies to polioviruses as an alternative to the neutralization test in tissue culture. - Edevåg, G (1995)
A poliovirus-binding inhibition test (PoBI test) was established for the quantitative determination of antibodies to polioviruses and was evaluated in comparison with the conventional neutralization test (NT). The first step of the PoBI test is an incubation of serial dilutions of test samples with inactivated poliovirus followed by the detection of free viral epitopes by a double antibody sandwich enzyme-linked immunosorbent assay with type-specific capture polyclonal antisera and type-specific neutralizing monoclonal indicator antibodies. A comparison of the PoBI test with the conventional NT for antibodies to all three types in 100 human serum samples showed excellent correlations (r > 0.95) over a wide range of antibody concentrations. The PoBI test, not necessitating live virus and tissue culture facilities, could be a simple alternative to the NT, and the principle of the assay is potentially applicable to other microbial systems.